Factors that Influence Student's Decision in Starting-up Service Franchise Business in Bandung. (20th January 2015) - Kristandy, Shintya Janice; Aldianto, Leo
Abstract: Starting a whole new business often seems to be too risky. There are too many uncertainties pertaining to the amount of capital required, the sales revenue potentially generated and the right management style required to achieve success. Franchise business, with an already well-established systems and operating procedures, provides a way for new entrepreneurs to invest in a more forecastable and profitable future. At the macro level, franchise business is like a vehicle driving the lifestyle and income of a population in the right direction for long term economics growth. Indonesia, being the one of the largest economies in Asia, offers excellent market potential for franchising. Having an adequate and proven systems already in place, franchise business is perceived as an appropriate stepping stone for building sustainable business environment in Indonesia. The allure of starting a franchise business in mitigating the uncertainties faced by an independent start-up to a large extent, therefore, is worth its weight in gold. This research aims to develop the know-how of starting-up effective franchise business to penetrate Indonesian market. The study hopes to establish a comprehensive guide for the increasing number of aspiring entrepreneurs to boost their confidence in starting up service franchise business in Bandung. This research uses both qualitative and quantitative research method. Through quantitative research, the author collected data through several surveys and questionnaires which were distributed among 100 business management students from several universities in Bandung such as Institute Technology Bandung, Parahyangan Catholic University, Padjajaran University, and Maranatha Christian University. Subsequently, qualitative research was also conducted to clarify ambiguous situations or discover ideas that may generate potentially-profitable business opportunities. Common data collection methods used in this qualitative research includes in-depth interview with related franchisor in the service industry. Researcher performed pre-test analysis to the data collected to ensure the constructs' validity and reliability. Data were then analyzed, computed and presented in various simplified forms (writing, graphics, tables, and numbers) for easy comprehension and interpretation. Our conclusion is that with adequate systems of franchise business already in place, it provides a suitable platform for the students to embark on their entrepreneurial journey. Purchasing a franchise business license is one common option. However, a substantial amount of attention has to be given to the franchise mechanism model i.e. factors such as: costs, controls, and termination/renewals of contracts. In the process of selecting the right franchise business, substantiate knowledge and careful review of the franchise agreement is of critical importance to prevent mislead and confusion. This paper will highlight and discuss these issues in further details.